1973
DOI: 10.1002/bjs.1800600513
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of regional enteritis in the gloucester area

Abstract: An epidemiological study has been made of regional enteritis in the Gloucester area during the period from 1 Jan., 1966, to 31 Dec., 1970. There were 19 cases in an average population of 253,000, giving an average incidence of new cases of 1.5 per 100,000 per year. There was a significant peak of cases in the 15–24 age‐group. The incidence in men was slightly higher than in women. There was a family history of ulcerative colitis in 2 cases. There were 3 cases of regional enteritis of the large bowel only, all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Such a steady rise in the incidence of the disease is England andWales (1950-1975).) Tresadern et al (1973) 1966-70 1-5 19 Aberdeen…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a steady rise in the incidence of the disease is England andWales (1950-1975).) Tresadern et al (1973) 1966-70 1-5 19 Aberdeen…”
Section: Discussionmentioning
confidence: 99%
“…In Britain the earliest epidemiological study from Oxford, 1951-60 (Evans andAcheson, 1965) found an incidence of 0-8 cases of 105/year and a comparable figure from our data for that period is approximately twice this value. The Gloucester study (Tresadern et al, 1973), which covered the period 1966-70, was relatively small and included only 19 cases; the incidence was 1-5 cases/105/year compared with 3 62 cases/year in Cardiff for the same period. One of the largest series came from Northern Ireland (Humphreys and Parks, 1975) where 159 cases were identified between 1966 and 1973; the cases were obtained from all six counties and the data were retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…In 1%5, Acheson [1] comprehensively reviewed the epidemiologic data on inflammatory bowel disease then available and in the same paper produced new data on the incidence and prevalence of inflammatory bowel disease in Oxford. Kyle and Blair [2] have described the epidemiology of Crohn's disease in northeast Scotland and, more recently, Tresadem, Gear, and Nichol [3] have presented similar data about Crohn's disease in the Gloucester area. These 3 studies present the only carefully circumscribed descriptions of the incidence of inflammatory bowel disease in British populations; other studies have been published, but they relate to patients seen and managed in specialist hospital units and, consequently, cannot give accurate information about the epidemiology of these diseases in a defined population.…”
mentioning
confidence: 92%
“…The relative risk to Europeans was 2.5 (95% confidence interval (CI) 0. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. There was no difference between the standardized incidence in Europeans and West Indians (Z = 0.45, NS), the relative risk to West Indians being 1.4 (95% CI 0.3-5.7).…”
Section: Resultsmentioning
confidence: 99%